Peran Guru Pendidikan Agama Kristen dalam Pendampingan Anak Berkebutuhan Khusus di Sekolah Inklusif - Ririn Liliyani Sioh; Anggreni Tamal Nenohai; Aprilia Mengga; Fernando Tualaka; Enjelili R Tega Wuasu; Maya Novita Mbura; Adriana Indra Santi Sole (INDO PUBLISHING, 2026)
This study aims to examine the role of Christian Religious Education (CRE) teachers in accompanying students with special needs in inclusive schools. Inclusive education requires CRE teachers to possess not only theological competence but also adaptive pedagogical skills and pastoral sensitivity toward the diversity of learners. Through a literature study method, this study analyzes various scholarly sources discussing the role of CRE teachers, characteristics of students with special needs, and inclusive practices in the context of Christian education. The results show that CRE teachers play a strategic role as adaptive educators, spiritual guides, social mediators, and collaborators within the inclusive school team. These roles are realized through love-based curriculum adaptation, personal pastoral approaches, and strengthening inclusive values rooted in Christian teaching. The implication is that Christian educational institutions need to strengthen the inclusive competencies of CRE teachers through training, professional mentoring, and responsive curriculum development.